IV Certamen Crono-Teatro (2017). Modalidad de tren. 4. Con(s)ejo rosa - Pygmaliòn, (Pygmalion. Revista de teatro general y comparado, 2025)
IV Certamen Crono-Teatro (2017). Modalidad de tren. 4. Con(s)ejo rosa